2001
DOI: 10.2143/ac.56.5.2005687
|View full text |Cite
|
Sign up to set email alerts
|

Iron status and itts relationship with lipid peroxidation in patients with acute myocardial infarction

Abstract: There was an association of higher iron status with increased lipid peroxidation in patients with myocardial infarction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 0 publications
1
9
1
Order By: Relevance
“…Despite being a potent antioxidant, NAC may have prooxidant properties when contacting iron ions [11]. In fact, it has been demonstrated that patients suffering an AMI increase serum iron levels, inducing lipid peroxidation after the ischemic event [1]. Since the reaction between iron and NAC may yield free radicals in biological systems [10,11], it can be .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Despite being a potent antioxidant, NAC may have prooxidant properties when contacting iron ions [11]. In fact, it has been demonstrated that patients suffering an AMI increase serum iron levels, inducing lipid peroxidation after the ischemic event [1]. Since the reaction between iron and NAC may yield free radicals in biological systems [10,11], it can be .…”
Section: Discussionmentioning
confidence: 99%
“…The DFX dose and regimen were chosen based on previous studies that have already employed this combination [17,18] and on the behavior of iron release post-AMI described in humans [1]. Cardiac function was assessed by echocardiography for 28 days, and an improvement could be seen only at the end of protocol for NAC/DFX treated rats, with a net improvement of 10 % in left ventricular ejection fraction and a substantial attenuation of systolic chamber dilation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…MDA levels can change with time following an acute MI. Erythrocyte MDA levels in patients increase immediately during an acute MI, peak on day 1 post‐MI, and then decline to 57% of the peak value by day 45 post‐MI [31]. In the present study, the different treatments started at 60 days post‐MI, so we expected TBARS levels in the ramipril group to be as low as, or lower than, those in the MI group.…”
Section: Discussionmentioning
confidence: 79%
“…According to these studies, ferritin may act as a pro-oxidant. Iron donates an electron to promote the formation of reactive oxygen species via the Fenton reaction and this causes oxidation of LDL, a trigger for the development of atherosclerotic CAD 6,7. Inflammation is associated with an abnormality in the redox state in the vasculature.…”
Section: Introductionmentioning
confidence: 99%